Direct Catalytic Conversion of Furfural to Furan‐derived Amines in the Presence of Ru‐based Catalyst. Issue 7 (18th February 2020) - Jiang, Shi; Ramdani, Wahiba; Muller, Eric; Ma, Changru; Pera‐Titus, Marc; Jerôme, François; De Oliveira Vigiera, Karine
Abstract: The production of amine intermediates from biomass is capturing increasing attention. Herein, a simple and efficient preparation of l furan‐derived amines was developed [e.g., 1‐(furan‐2‐yl)‐4‐methylpentan‐2‐amine] with high yield (up to 95 %) from ( E )‐1‐(furan‐2‐yl)‐5‐methylhex‐1‐en‐3‐one. The catalyst used was Ru/C, and it was recyclable up to the fourth cycle. To further realize cost‐efficiency, a one‐reactor tandem concept was attempted. To this aim direct reaction from furfural was investigated. A high yield (74 %) towards 1‐(furan‐2‐yl)‐4‐methylpentan‐2‐amine could be achieved starting directly from furfural in the presence of methyl isobutyl ketone, NH3, H2, and Ru/C catalyst. Abstract : Green amines : Catalytic conversion of furfural to primary amines is achieved with high yield (74 %) by a one‐reactor two‐step process in the presence of Amberlyst 16 and Ru/C based catalysts. The hydrogenation of C=C bonds together with the reductive amination of carbonyl groups at mild reaction conditions is performed using ammonia and hydrogen.